Photodynamic therapy in the treatment of early squamous cell carcinoma of the oral cavity (Panacea Journal of Medical Sciences, 2022)
Oral squamous cell carcinoma (OSCC) is the most common subtype of malignant tumor of the oral cavity. In India, oral cancer is the commonest cancer in males. Although there have been great advances in the diagnosisand treatment of OSCC in recent years, the 5-year survival rate for advanced oral cancer patients has remainedapproximately 20.0%.